Preparing children with disabilities for school from pre-school teachers' perspective - Kojić, Miroslava B; Markov, Zagorka T; Kojić-Grandić, Smiljana S (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
In this paper, preparing children with disabilities for school starts from a multidimensional and complex process that lasts much longer than formal preparation, which, according to legal regulations, lasts one year. This process requires a personalized approach to a child with a developmental disability, which is based on the child's current level of development and achievement, not developmental norms for a specific calendar age. It starts with the child's current abilities and by expanding and upgrading it`s knowledge, skills and habits. The aim of this paper is to determine the specifics of preparing children with disabilities to attend school in mainstream kindergarten from the perspective of the pre-school teacher. For the purpose of the research, a questionnaire was designed to assess the pre-school teachers` observations about preparing children with disabilities for school. The results of the research show that, from the teachers` perspective, preparing children with developmental disabilities to attend school carries a number of specifics that require a thorough plan and program of activities. This plan is based on (a) personalized approach to the child, individualization or implementation of IEP, (b) teamwork in pre-school and (v) additional support for children, parents and educators, implemented by law specialists in speech and speech therapists. A significant role in the identified factors for preparing children with developmental disabilities for school is played by peers of typical development.
Keywords: teamwork; additional support; IEP; preparation for school; children with disabilities